Variability in phenotype and response to treatment in chronic nonbacterial osteomyelitis; the Irish experience of a national cohort - Daire O'Leary; Anthony G. Wilson; Emma-Jane MacDermott; Clodagh Lowry; Orla G. Killeen (BMC, 2021)
Abstract Background Chronic nonbacterial osteomyelitis (CNO) is an autoinflammatory disease affecting bone with considerable phenotypic heterogeneity and variable association with other autoinflammatory conditions. Disease pathogenesis is incompletely understood, and treatment protocols vary between physicians with no clinical treatment guidelines available prior to 2017. Although CNO was previously considered benign, it is now clear that long-term sequelae do occur. The aim of this study is to provide a detailed phenotypic description of children and adolescents with CNO who attended tertiary paediatric rheumatology services in Ireland between September 2017 and September 2019, their disease course, treatment and outcomes. Methods This study involved retrospective review of clinical notes, laboratory, radiology and histology results of Irish children and adolescents with CNO who are currently attending tertiary paediatric rheumatology services. The Bristol diagnostic criteria were applied retrospectively; only patients who met these criteria were included. Criteria for remission and partial response were based on the Childhood Arthritis and Rheumatology Research Alliance (CARRA) criteria for treatment failure. Results Forty-four children and adolescents were recruited. Demographics in terms of age of onset, gender and number of sites were similar to those previously reported. Overall, 18/44 (40.9%) had extraosseous manifestations associated with CNO; 12/44 (27.2%) had cutaneous involvement. All patients received a regular nonsteroidal anti-inflammatory drug (NSAID) after diagnosis with 27/44 (61.4%) requiring at least 1 second-line medication. Second-line agents used in this cohort were bisphosphonates, methotrexate and TNF-blockers. No patients received systemic corticosteroids. Conclusion This national cohort showed a high prevalence of extraosseous involvement and a low response rate to NSAID treatment. This may reflect a more inflammatory phenotype and highlights the need to define different subtypes of CNO.